The relevance of commuting zones for regional spending efficiency - Afonso, António (2013)
We use Data Envelopment Analysis (DEA) efficiency scores to show that clustering municipalities into encompassing regional clusters improves spending efficiency of single stand-alone municipalities. We propose a new geographic aggregation based on municipalities-to-municipalities commuting flows, defined using hierarchical cluster analysis. Our example for Portugal shows that from an output oriented perspective, between 85 and 95 percent of municipalities would increase their efficiency scores, while from an input oriented perspective, between 81 and 97 percent of municipalities would also be better off in terms of efficiency. Our strategy and results are naturally quite relevant in a context of public spending control.